2019
DOI: 10.1007/s11627-019-09963-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved plant regeneration in callus cultures of Sorghum bicolor (L.) Moench

Abstract: Sorghum bicolor is a recalcitrant species for tissue culture regeneration and genetic transformation. Browning of explants is one of the factors limiting organ and tissue cultures. To overcome this, callus tissue was initiated from the shoot tips of in vitro germinating seeds (S. bicolor cv. Róna 1), and then cultured on modified MS media (Murashige and Skoog in Physiol Plant 15:473-497, 1962). In the first experiment, we tested callus induction on several media supplemented with casein hydrolysate, polyvinylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
(34 reference statements)
0
15
0
3
Order By: Relevance
“…Several studies have targeted the genetic control of in vitro responsiveness in a variety of plants. Many have involved QTL identification [34,65,[79][80][81][82][83], and more recently, GWAS [31,36,84]. These studies have identified several genetic loci and candidate genes associated with various aspects of in vitro responsiveness.…”
Section: Albino Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have targeted the genetic control of in vitro responsiveness in a variety of plants. Many have involved QTL identification [34,65,[79][80][81][82][83], and more recently, GWAS [31,36,84]. These studies have identified several genetic loci and candidate genes associated with various aspects of in vitro responsiveness.…”
Section: Albino Regenerationmentioning
confidence: 99%
“…These studies have shown that sorghum in vitro responsiveness displays genotype-dependency [27][28][29], with sorghum considered to be relatively recalcitrant to in vitro manipulation, due to factors like genotype-dependent phenolic production and tissue browning. Efforts to improve this recalcitrance have used different tissue culture media modifications to improve cell survival [28,30,31] and subsequent regeneration, as well as the overexpression of Baby Boom and Wuschel genes to stimulate the embryogenic potential of explant cells and improve regeneration [32]. An understanding of the genetics associated with tissue culture/in vitro responsiveness would facilitate breeding for improved regenerability/transformability, but also provide for a greater understanding of sorghum developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the media, carbon sources also play an important role in plant organogenesis in vitro. Exogenous carbon sources added into the media can influence organ differentiation and plant regeneration efficiency in vitro [10].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon source most often used in tissue culture is sucrose, because it is the most effective carbon source compared to other types of sugars. According to the research of [10] the use of media with sucrose is most effective against plant induction. [11] mention the concentration of sucrose influences the continuity of cell growth, besides that [12] said that sucrose plays an important role in the induction of cells and energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that sorghum in vitro responsiveness displays genotype-dependency (Kaeppler and Pedersen 1997, Liu et al 2015, Omer et al 2018), with sorghum considered to be relatively recalcitrant to in vitro manipulation, due to factors like genotype-dependent phenolic production and tissue browning. Efforts to improve this recalcitrance have used different tissue culture media modifications to improve cell survival (Elkonin et al 1995, Liu et al 2015, Dreger et al 2019) and subsequent regeneration, as well as the overexpression of Baby Boom and Wuschel genes to stimulate the embryogenic potential of explant cells, and improve regeneration (Lowe et al 2016). An understanding of the genetics associated with tissue culture/in vitro responsiveness would facilitate breeding for improved regenerability/transformability, but also provide for a greater understanding of sorghum developmental processes.…”
Section: Introductionmentioning
confidence: 99%